Mr. Grex of Monte Carlo - Oppenheim, Edward Phillips (Saga Egmont, 2021)
Set in the glamour of pre-WWI Monaco, ‘Mr. Grex of Monte Carlo’ follows the exploits of Sir Hunterleys. An English MP, he discovers his estranged wife in the company of the Draconmeyers, who he had expressly forbidden her to associate with. The fate of Europe and of his marriage rests on his shoulders – will Hunterley be able to save them both? A fascinating look into the bubbling tensions of pre-war Europe in this intriguing novel from E. Phillips Oppenheim.